Bribery, motivations for bribery and life satisfaction in transitional countries. (March 2020) - Hinks, Timothy
Highlights: First paper to test is type of motivation to bribe and life satisfaction are correlated. Those who were extorted by public officials reported lower life satisfaction levels. People who made an informal payment to speed things up reported higher life satisfaction. The public service that is used and income-level of the person, impacts on whether type of bribe is associated with life satisfaction. Abstract: The focus on bribery and corruption and its impact on life satisfaction is relatively new in the economics and development studies literature. This paper contributes to this emerging field by asking whether reasons for making informal payments are correlated with life satisfaction. We find that paying bribes negatively correlates with life satisfaction and that those who were extorted by public officials or made an informal payment since they thought it was expected of them reported lower life satisfaction levels. We also find that those who made an informal payment to speed things up or who thought of the payment as a gift reported higher life satisfaction. Reasons for bribery differ in their associated significance with life satisfaction by public service that is used and by income group. For example people who instigated informal payments to public officials in the civil courts report higher life satisfaction bringing into question the integrity of judicial systems in transitional countries.